The Spanish War of Independence in Spanish Literature (1814-1914) La Guerra de la Independencia en la literatura española (1814-1914) - Ana María FREIRE LÓPEZ (Cuadernos Dieciochistas)
The author, who in earlier works studied how the narrative and drama produced after the Spanish War of Independence transmitted the events of that war and the image of its protagonists, now traces in this article an outline of how literature portrayed that war and its significance, without going into the formal aspects of the works or other issues already dealt with in prior studies. After a brief presentation of the War of Independence as a literary topic between 1814 and 1914, this article focuses on three aspects: what persisted of the view of those occurrences with respect to the literature written during the war; what changed since 1814 in their transmission, and what was new in the literature about the war written after it had ended. RESUMEN: La autora, que en otros trabajos ha estudiado cómo transmitieron la narrativa y el teatro posteriores a la contienda los sucesos de la Guerra de la Independencia y la imagen de sus protagonistas, traza en este artículo un panorama general de la visión que la literatura dio de aquella guerra y de su significado, sin detenerse en los aspectos formales de las obras u otras cuestiones, que ha tratado en los mencionados trabajos. Después de una breve presentación de la Guerra de la Independencia como asunto literario entre 1814 y 1914, centra su atención en tres aspectos: qué perdura a lo largo de esos cien años en la visión de aquellos acontecimientos con respecto a la literatura que se escribió durante la guerra; qué cambia, desde 1814, en la transmisión de los mismos; y qué hay de nuevo en esa literatura sobre la Guerra de la Independencia escrita después de su terminación.